Exfoliation of covalent organic frameworks into MnO2-loaded ultrathin nanosheets as efficient cathode catalysts for Li-CO2 batteries - Jiang, Cheng; Zhang, Yu; Zhang, Mi; Ma, Na-Na; Gao, Guang-Kuo; Wang, Jian-Hui; Zhang, Meng-Meng; Chen, Yifa; Li, Shun-Li; Lan, Ya-Qian (Cell reports physical science, 2021)
Rechargeable Li-CO2 batteries have been studied extensively as an attractive strategy for simultaneous energy storage and CO2 fixation to address the global environmental and energy crisis. However, state-of-the-art Li-CO2 systems still suffer from unsatisfactory performance. Here, we successfully exfoliated quinone-based covalent organic frameworks (COFs) into large-scale and ultrathin MnO2/2,6-diaminoanthraquinone-2,4,6-triformylphloroglucinol (DQTP)-COF-nanosheet (NS) hybrid materials. The obtained ultrathin nanosheets (as thin as 1.87 nm) synergistically integrate quinone-COF-NSs with MnO2 and serve as powerful cathode catalysts in Li-CO2 batteries. MnO2/DQTP-COF-NS-3 has a high discharge capacity of 42,802 mAh/g at 200 mA/g. Additionally, it is durable for higher-stress test with a negligible change of overpotential from 500 to 1,000 mA/g and is discharged/charged rapidly for 120 cycles at 1 A/g. Moreover, the CO2 activation mechanism is discussed and supported by density functional theory (DFT) calculations. This work may pave a new way for exploring porous crystalline materials as efficient cathode catalysts for Li-CO2 batteries. [Display omitted] Exfoliation of quinone-based COFs into large-scale and ultrathin nanosheetsMnO2/DQTP-COF-NS-3 can be applied as high-performance cathode catalystDFT study supports the vital role of quinone group in CO2 reduction reaction Jiang et al. report exfoliation of quinone-based covalent organic frameworks (COFs) into large-scale and ultrathin MnO2/DQTP-COF-nanosheet hybrid materials. The ultrathin nanosheets synergistically integrate quinone-COFs with MnO2 and serve as cathode catalysts in Li-CO2 batteries with a high discharge capacity (42,802 mAh/g at 200 mA/g) and good durability in rapid cycling tests.